Misleading Theologies of Wealth and Poverty in the Context of Faith - Ngwobia, Ukoha (Addressing Contextual Misleading Theologies in Africa Today, 2020)
[Book abstract] This volume offers constructive and contextual theological discussions that uphold Christian teaching and beliefs to promote a life with dignity in the African continent, based on practical theological beliefs. The authors discuss different thematic topics among which issues of health and healing that are pertinent in Africa and have perpetuated misleading theologies. The book also addresses issues of wealth and poverty in the context of faith which is critical in the context of misleading theologies. It articulates how prosperity gospel has propelled a paradigm shift in understanding material prosperity as a reflection of one’s faith, a blessing and poverty as lack of faith as well as a curse. The issue of personalization of power and authority in the contemporary emerging theologies that lead to misleading practices has been contrasted with power and authority from God that take into account the respect and dignity of human beings.
paid